2007
DOI: 10.1021/ar600021z
|View full text |Cite
|
Sign up to set email alerts
|

New Catalytic Reactions of Oxa- and Azabicyclic Alkenes

Abstract: Bicyclic alkenes, including oxa- and azabenzonorbornadienes and their derivatives, can be readily activated by transition metal complexes face-selectively due to their unsymmetrical bicyclic structure and the intrinsic angle strain on the carbon-carbon double bond. We have developed several stereo-, regio-, and chemoselective reactions catalyzed by nickel and palladium complexes using these bicyclic alkenes as substrates, providing a unique means of constructing a variety of synthetically useful carbocycles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(62 citation statements)
references
References 62 publications
1
58
0
3
Order By: Relevance
“…Thus, we focused on a synthetic equivalent of arynes, [2.2.1]oxabicyclic alkenes, as monomers for polymerization. Although [2.2.1]oxabicyclic alkenes are useful building blocks and intermediates in organic synthesis, 89,90 they have rarely been used as monomers for polymerization. 9194 Our initial hypothesis is shown in Figure 17.…”
Section: Formal Aryne Polymerizationmentioning
confidence: 99%
“…Thus, we focused on a synthetic equivalent of arynes, [2.2.1]oxabicyclic alkenes, as monomers for polymerization. Although [2.2.1]oxabicyclic alkenes are useful building blocks and intermediates in organic synthesis, 89,90 they have rarely been used as monomers for polymerization. 9194 Our initial hypothesis is shown in Figure 17.…”
Section: Formal Aryne Polymerizationmentioning
confidence: 99%
“…Intramolecular nucleophilic addition of the C À Co bond to the amide carbonyl group followed by protodemetalation and elimination of AQ provides the final ketone product and regenerates the catalytically active Co III species.I ti sn oteworthy that the insertion of 7-oxabenzonorbornadiene (2a) into intermediate I to give II generally occurs only at the exo face of 2a,r esulting in the observed stereochemistry. [16] Furthermore,intermediate II features no suitable b-hydrogen atoms for elimination to give an olefination product, [7] and the combined steric hindrance of the AQ moiety and bicyclic alkene 2a prevents the direct reductive elimination to as ixmembered lactam. [6] In summary,wehave developed acobalt-catalyzed [3+ +2] cycloaddition of aromatic/vinylic secondary amides with bicyclica lkenes.T he reaction proceeds by coordinationassisted C À Hactivation, alkene insertion, and intramolecular nucleophilic addition.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…To demonstrate the utility of oxabicycles 3 as synthetic building blocks, we investigated the ring‐opening reaction of 3 a with aryl iodides in the presence of organometallic reagents4a (Scheme ). Cheng and co‐workers have previously shown that this type of coupling reaction can be achieved by using a catalytic amount of a Pd II complex, giving rise to cis ‐dihydronaphthol derivatives 12.…”
Section: Methodsmentioning
confidence: 99%